Papua Conflict Reconciliation Model and Strategies - Samparisna O. D. Koibur (Budapest International Research and Critics University, 2021)
At a glance, the Papuan conflict is a vertical conflict that has lasted more than 50 years. The main cause of this conflict is the desire for “Free Papua” which is supported by the Free Papua Movement (OPM). Conflicts also escalated over the issue of race and discrimination against Papuan students in Surabaya and Malang in August 2019. Negotiation is the Indonesian government's best option for resolving disputes in Papua. The main purpose of this article is to find the best solution for dispute resolution in Papua in terms of the terms that must be carried out and the negotiation process. This study uses a qualitative methodology to investigate social phenomena in society that occur naturally without engineering or laboratory work. This approach provides descriptive data in the form of descriptive or verbal words that describe conditions, situations, or certain different variables. The data collection technique is to use a literature search to obtain the required data. As a result, the Papua conflict negotiation process involved internal parties (central/regional government, KKB/OPM, traditional/religious leaders, civil society) and external parties (freeport), and became the main demand. Indicates that it is an independent Papua. Negotiations have been time consuming and faced many obstacles, but we continue to strive to reach a mutually beneficial solution. Dialogue between Jakarta and Papua should better reflect the cultural values of the Papuan people.